Preface: 2nd International Conference on Energy Research and Environmental Technology (ERET 2024) - Geordie, Oswald; Wan, Jia (Transactions on Environment, Energy and Earth Sciences, 2024)
The 2024 2nd International Conference on Energy Research and Environmental Technology (ERET 2024) was held during August 24-25, 2024 in Detroit, USA. This conference aims to bring together academic scientists, leading engineers, industry researchers and scholar students to exchange and share their experiences and research results about all aspects of energy research, energy materials, hydrogen and fuel cell, pollution control, environmental technology, and ecological system, and will discuss the practical challenges encountered and the solutions adopted. This conference becomes a platform for the delegates from different countries to meet and gain fruitful results. Many experts and researchers in related fields attended ERET 2024 to share their innovative ideas, discuss the state-of-art methods, exchange their experiences, and establish beneficial collaborations. Delegates enjoyed the good time they had in the conference. The papers collected for publication are of high quality and related to different areas. The conference ended successfully and all the delegates looked forward to attending the next meeting. The success of ERET 2024 has relied on many people’s efforts and contributions. Many thanks are extended to the colleagues and students for their assistance in organizing the conference. The reviewers have helped not only review the papers but also provide valuable comments to improve the quality of the papers. Their efforts and assistance are prominent in making the conference a success. The success of the conference is a natural outcome of their contributions and assistance. The ERET Conference Committee Detroit, USA